The profile of the elderly in Primary Health Care of a middle city Brazil - Medeiros, Kaio Keomma Aires Silva (2018)
ABSTRACT: The aim of this study was to describe the profile about the elderly in Primary Health Care in Brazilian meddle city. Cross-sectional study with 162 participants. It was verified that majority of women, advanced age, reduced per capita income, high prevalence of cardiovascular diseases and most of them obtained service on the last on the last attempt. The reality that circumscribes the elderly connected with primary health care is permeated by positive and negative aspects.